2017
DOI: 10.1093/heapro/dax088
|View full text |Cite
|
Sign up to set email alerts
|

Poverty-related diseases: factors that predict coping in two Cameroonian settings

Abstract: In this paper, we explore the connection between poverty and health (poverty-related diseases: PRDs) by investigating the factors that play a role in how two groups of people in Cameroon cope with health challenges: workers in a large agro-industrial organization (living in 'camps') and students in two major universities (living on 'campuses'). We investigated factors reported in the literature as being associated with coping, summarized under the 'salutogenic umbrella', as well as demographic, social and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…They are impoverished and also lack access to education, information, financial resources and quality healthcare. The relationship between wealth and health services uptake and health outcomes in developing countries has been established in the literature [4][5][6][7][8][9]. Fagbamigbe et al found that persons from wealthier households in Nigeria had a higher propensity of utilizing health services [6].…”
Section: Introductionmentioning
confidence: 99%
“…They are impoverished and also lack access to education, information, financial resources and quality healthcare. The relationship between wealth and health services uptake and health outcomes in developing countries has been established in the literature [4][5][6][7][8][9]. Fagbamigbe et al found that persons from wealthier households in Nigeria had a higher propensity of utilizing health services [6].…”
Section: Introductionmentioning
confidence: 99%